Communication Skills Important to Minnesota County Extension Agents - Earl E. McDowell; Jeanne L. Mizuno (Journal of Applied Communications, 1987)
Communication skills used and required in various organizational contexts have been the subject of many studies in recent years. In order to study such skills, an instrument is needed which is reliable and easily adapted to fit specific organizational settings.